Antibacterial and corrosion-resistant EVA (Ethylene Vinyl Acetate) liquid storage bag material and preparation method thereof

By using core-shell structure antibacterial/corrosion-resistant fillers, and modified sodium alginate aerogel and polyurethane loaded with silver nanoclusters, the problem of insufficient antibacterial, compatibility and corrosion resistance of the material is solved, and efficient antibacterial and chemical corrosion resistance is achieved.

CN119842142AActive Publication Date: 2025-04-18JIANGSU HUIMING MEDICAL EQUIPMENT CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510347155.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-24
Publication Date
2025-04-18
Estimated Expiration
2045-03-24

AI Technical Summary

Technical Problem

The EVA liquid storage bag material itself does not have antibacterial properties, and there are problems such as poor material compatibility and insufficient chemical corrosion resistance.

Method used

Antibacterial/corrosion-resistant filler with core-shell structure, modified sodium alginate aerogel loaded with silver nanoclusters is used as the core and polyurethane is used as the shell. The load density and stability of silver nanoclusters are improved through the "egg box" structure, and the flexibility and mechanical strength of the material are improved by the coating of polyurethane.

Benefits of technology

The long-term antibacterial and chemical corrosion resistance of EVA liquid storage bag materials is achieved, and the stability and compatibility of the material are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention provides an antibacterial and corrosion-resistant EVA (Ethylene Vinyl Acetate) liquid storage bag material and a preparation method thereof. The EVA liquid storage bag material is obtained by blending an antibacterial / corrosion-resistant filler with a core-shell structure and EVA, the preparation method comprises the following steps: uniformly mixing the antibacterial / corrosion-resistant filler with the core-shell structure and the EVA base material; and putting the mixture into a mixing mill for mixing at the mixing temperature of 110 DEG C and the double-roller rotating speed of 100 r / min for two times, and mixing for 10 minutes each time, so as to obtain the composite material. The antibacterial / corrosion-resistant filler with a core-shell structure is adopted, the modified sodium alginate aerogel loaded with the silver nanoclusters is used as a core, polyurethane is used as a shell, and the antibacterial and corrosion-resistant effects are achieved at the same time; alpha-L-guluronic acid in the sodium alginate aerogel can be chelated with the silver nanoclusters to form an egg box structure, on one hand, the silver nanoclusters are loaded on the aerogel, the nanometer aggregation degree of the silver nanoclusters can be greatly improved, high-density loading is achieved, the silver nanoclusters and the sodium alginate aerogel are combined more firmly through the egg box, and the silver nanoclusters and the sodium alginate aerogel are combined more firmly. And long-term stability can be maintained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of medical materials, and in particular to an antibacterial and corrosion-resistant EVA liquid storage bag material and a preparation method thereof. Background Art

[0002] Ethylene-vinyl acetate copolymer (EVA) is a highly branched random copolymer obtained by copolymerization of non-polar ethylene monomer and polar vinyl acetate monomer. The introduction of VA monomer in the EVA copolymer chain segment increases the branching degree of the chain segment, affects the crystallization ability, and reduces its crystallinity. EVA copolymer is a semi-crystalline copolymer composed of crystalline phase and amorphous phase; EVA copolymer can be used in packaging protection materials, sealing materials, medical catheters, insulating films and accessories, etc.; EVA copolymer is non-toxic and harmless, and has good performance in optical properties, weather resistance, processability, flexibility, etc. However, it does not have antibacterial properties and has the problem of poor material compatibility. At the same time, when used as a liquid storage bag material, it needs to have good chemical corrosion resistance. Therefore, the research and development of a suitable EVA material that can achieve long-term antibacterial and chemical corrosion resistance is the focus of research. Summary of the invention

[0003] Technical problem to be solved: In view of the above technical problems, the present invention provides an antibacterial and corrosion-resistant EVA liquid storage bag material and a preparation method thereof, adopts an antibacterial / corrosion-resistant filler with a core-shell structure, with modified sodium alginate aerogel loaded with silver nanoclusters as the core and polyurethane as the shell, so as to achieve the effects of simultaneous antibacterial and corrosion resistance; the α-L-guluronic acid in the sodium alginate aerogel can chelate with the silver nanoclusters to form an "egg-box" structure. On the one hand, loading the silver nanoclusters on the aerogel can greatly improve the nano-aggregation degree of the silver nanoclusters and achieve high-density loading, and the "egg-box" makes the silver nanoclusters and the sodium alginate aerogel more firmly combined and can maintain long-term stability. On the other hand, the silver nanoclusters protect the internal pores and wire diameters of the sodium alginate aerogel, greatly improving the mechanical properties of the sodium alginate.

[0004] Technical solution: An antibacterial and corrosion-resistant EVA liquid storage bag material, wherein the EVA liquid storage bag material is obtained by blending an antibacterial / corrosion-resistant filler with a core-shell structure and EVA; the mass ratio of the antibacterial / corrosion-resistant filler with the core-shell structure to EVA is (3-5):100.

[0005] Furthermore, the preparation method of the core-shell structured antibacterial / corrosion-resistant filler is: Step 1: Take sodium alginate, add water and stir to obtain a 1.5wt.% sodium alginate aqueous solution; Step 2: Add 2wt.% ethylenediamine solution, mix and stir evenly to obtain a modified sodium alginate aqueous solution; Step 3: Mix the aldehyde-modified nanocellulose solution, the silver ammonia solution and the glutathione solution and stir them thoroughly to react, thereby obtaining silver nanocluster micelles; Step 4: Add the silver nanocluster micelles into the modified sodium alginate aqueous solution, ultrasonicate for 30-60 minutes, and then stand for 40 minutes; Step 5: slowly pour into anhydrous ethanol solution to obtain modified sodium alginate wet gel loaded with silver nanoclusters, let stand for 1 hour, and filter; Step 6: rinse with deionized water, pre-freeze for 24 hours, and freeze-dry to obtain modified sodium alginate aerogel loaded with silver nanoclusters; Step 7: crushing the modified sodium alginate aerogel loaded with silver nanoclusters and passing it through a 400-mesh sieve to obtain aerogel particles; Step 8: dissolving polyurethane in N,N-dimethylformamide to obtain a polyurethane solution, impregnating aerogel particles therein, and maintaining the solution under vacuum until bubbles escape; Step 9: Take out and dry thoroughly to obtain the antibacterial / corrosion-resistant filler with a core-shell structure.

[0006] Furthermore, the mass ratio of the sodium alginate in step 1 to the ethylenediamine in step 2 is 10:1.

[0007] Furthermore, the preparation method of the aldehyde-modified nanocellulose in step 3 is as follows: (1) Disperse cellulose in a mixed solution of sodium hydroxide, urea and thiourea, stir vigorously for 30 min, cool to -10 °C, and centrifuge at 11000 rpm for 20 min to obtain a cellulose solution; (2) Slowly dripping deionized water into the cellulose solution while slowly stirring to obtain a milky white suspension, and washing the suspension with deionized water until the pH value is 7; (3) Ultrasonication at 600 W for 30 min to obtain nanocellulose; (4) adding sodium periodate to a 10 mg / mL nanocellulose solution, adjusting the pH value to 4.5, stirring at 40 °C for 4 h, and centrifuging and washing to obtain dialdehyde nanocellulose; (5) Disperse the dialdehyde nanocellulose in deionized water, add 25 wt% glutaraldehyde solution, stir and react at 70 °C for 30 min, and wash by centrifugation with deionized water to obtain aldehyde-modified nanocellulose.

[0008] Furthermore, in the mixed solution of sodium hydroxide, urea and thiourea in step (1), the concentration of sodium hydroxide, the concentration of urea and the concentration of thiourea are 8 wt %, 8 wt % and 6.5 wt %.

[0009] Furthermore, in step (4), the mass ratio of sodium periodate to nanocellulose is 2:1.

[0010] Furthermore, in step 3, the molar ratio of the aldehyde content of the aldehyde-modified nanocellulose, the silver-ammonia complex ions in the silver-ammonia solution, and glutathione is 1:(3-8):(5-10).

[0011] Furthermore, in step 4, the volume ratio of the silver nanocluster micelles to the modified sodium alginate aqueous solution is 1:(1-3).

[0012] Furthermore, the concentration of the polyurethane solution in step 8 is 0.2-0.4 g / mL.

[0013] The method for preparing the above-mentioned antibacterial and corrosion-resistant EVA liquid storage bag material comprises the following steps: (1) Mixing the core-shell structured antibacterial / corrosion-resistant filler and the EVA substrate uniformly; (2) Place the mixture in a mixer and mix it at a mixing temperature of 110°C and a double-roll speed of 100 r / min. Mix it twice, with each mixing time being 10 min. Beneficial Effects

[0014] The invention adopts an antibacterial / corrosion-resistant filler with a core-shell structure, with modified sodium alginate aerogel loaded with silver nanoclusters as the core and polyurethane as the shell, so as to achieve the effects of both antibacterial and corrosion resistance.

[0015] The α-L-guluronic acid in the sodium alginate aerogel of the present invention can chelate with the silver nanoclusters to form an "egg-box" structure. On the one hand, loading the silver nanoclusters on the aerogel can greatly improve the nano-aggregation degree of the silver nanoclusters and achieve high-density loading. The "egg-box" makes the combination of the silver nanoclusters and the sodium alginate aerogel more firmly and can maintain long-term stability. On the other hand, the silver nanoclusters protect the internal pores and wire diameters of the sodium alginate aerogel, thereby greatly improving the mechanical properties of the sodium alginate.

[0016] In the present invention, sodium alginate is modified with ethylenediamine to obtain -NH2. The -NH-CO-NH- bond formed by the reaction of polyurethane and -NH2 has a high bond energy, so that the two are closely combined, the contact area between particles constituting the skeleton structure is increased, and the stability of the overall structure of the aerogel is improved.

[0017] Aerogel is brittle and fragile. By wrapping the aerogel in polyurethane and introducing the flexible molecular chains of polyurethane, the microstructure of the aerogel can be effectively protected, and the flexibility and mechanical strength of the material can be enhanced. The hydroxyl groups on the sodium alginate aerogel can form hydrogen bonds with the hydrophilic groups on the hard segment of the polyurethane, thereby increasing the cross-linking density and having an excellent anti-corrosion effect.

[0018] The present invention uses polyurethane as the shell, which can also improve the dispersibility of the core-shell structure and the compatibility with EVA. DETAILED DESCRIPTION Example 1

[0019] The preparation method of aldehyde-modified nanocellulose is as follows: (1) Dispersing cellulose in a mixed solution of sodium hydroxide, urea and thiourea, wherein the concentration of sodium hydroxide, urea and thiourea in the mixed solution is 8 wt.%, 8 wt.%, and 6.5 wt.%, and vigorously stirring for 30 min, cooling to -10 °C, and centrifuging at 11000 rpm for 20 min to obtain a cellulose solution; (2) Slowly dripping deionized water into the cellulose solution while slowly stirring to obtain a milky white suspension, and washing the suspension with deionized water until the pH value is 7; (3) Ultrasonication at 600 W for 30 min to obtain nanocellulose; (4) adding sodium periodate to a 10 mg / mL nanocellulose solution, with a mass ratio of sodium periodate to nanocellulose of 2:1, adjusting the pH value to 4.5, stirring at 40 °C for 4 h, and centrifuging and washing to obtain dialdehyde nanocellulose; (5) Disperse the dialdehyde nanocellulose in deionized water, add 25 wt.% glutaraldehyde solution, stir and react at 70 °C for 30 min, and wash by centrifugation with deionized water to obtain aldehyde-modified nanocellulose. Example 2

[0020] The preparation method of the core-shell structured antibacterial / corrosion-resistant filler is as follows: Step 1: Take 10 g of sodium alginate, add water and stir to obtain a 1.5 wt.% sodium alginate aqueous solution; Step 2: Take 1 g of ethylenediamine, add water and stir to obtain a 2 wt.% ethylenediamine solution, mix the sodium alginate aqueous solution and the ethylenediamine solution and stir evenly to obtain a modified sodium alginate aqueous solution; Step 3: mixing the aldehyde-modified nanocellulose solution, the silver-ammonia solution and the glutathione solution and stirring them thoroughly to obtain silver nanocluster micelles; wherein the molar ratio of the aldehyde content of the aldehyde-modified nanocellulose, the silver-ammonia complex ions in the silver-ammonia solution and the glutathione is 1:5:7; Step 4: adding the silver nanocluster micelles to the modified sodium alginate aqueous solution, the volume ratio of the silver nanocluster micelles to the modified sodium alginate aqueous solution is 1:1, ultrasonically treating for 50 minutes and then standing for 40 minutes; Step 5: slowly pour into anhydrous ethanol solution to obtain modified sodium alginate wet gel loaded with silver nanoclusters, let stand for 1 hour, and filter; Step 6: rinse with deionized water, pre-freeze for 24 hours, and freeze-dry to obtain modified sodium alginate aerogel loaded with silver nanoclusters; Step 7: crushing the modified sodium alginate aerogel loaded with silver nanoclusters and passing it through a 400-mesh sieve to obtain aerogel particles; Step 8: dissolving polyurethane in N,N-dimethylformamide to obtain a polyurethane solution with a concentration of 0.3 g / mL, immersing aerogel particles therein, and maintaining the solution under vacuum until bubbles escape; Step 9: Take out and dry thoroughly to obtain the antibacterial / corrosion-resistant filler with a core-shell structure. Example 3

[0021] The preparation method of the core-shell structured antibacterial / corrosion-resistant filler is as follows: Step 1: Take 10 g of sodium alginate, add water and stir to obtain a 1.5 wt.% sodium alginate aqueous solution; Step 2: Take 1 g of ethylenediamine, add water and stir to obtain a 2 wt.% ethylenediamine solution, mix the sodium alginate aqueous solution and the ethylenediamine solution and stir evenly to obtain a modified sodium alginate aqueous solution; Step 3: mixing the aldehyde-modified nanocellulose solution, the silver-ammonia solution and the glutathione solution and stirring them thoroughly to obtain silver nanocluster micelles; wherein the molar ratio of the aldehyde content of the aldehyde-modified nanocellulose, the silver-ammonia complex ions in the silver-ammonia solution and the glutathione is 1:5:7; Step 4: adding the silver nanocluster micelles to the modified sodium alginate aqueous solution, the volume ratio of the silver nanocluster micelles to the modified sodium alginate aqueous solution is 1:2, ultrasonically treating for 50 minutes and then standing for 40 minutes; Step 5: slowly pour into anhydrous ethanol solution to obtain modified sodium alginate wet gel loaded with silver nanoclusters, let stand for 1 hour, and filter; Step 6: rinse with deionized water, pre-freeze for 24 hours, and freeze-dry to obtain modified sodium alginate aerogel loaded with silver nanoclusters; Step 7: crushing the modified sodium alginate aerogel loaded with silver nanoclusters and passing it through a 400-mesh sieve to obtain aerogel particles; Step 8: dissolving polyurethane in N,N-dimethylformamide to obtain a polyurethane solution with a concentration of 0.3 g / mL, immersing aerogel particles therein, and maintaining the solution under vacuum until bubbles escape; Step 9: Take out and dry thoroughly to obtain the antibacterial / corrosion-resistant filler with a core-shell structure. Example 4

[0022] The preparation method of the core-shell structured antibacterial / corrosion-resistant filler is as follows: Step 1: Take 10 g of sodium alginate, add water and stir to obtain a 1.5 wt.% sodium alginate aqueous solution; Step 2: Take 1 g of ethylenediamine, add water and stir to obtain a 2 wt.% ethylenediamine solution, mix the sodium alginate aqueous solution and the ethylenediamine solution and stir evenly to obtain a modified sodium alginate aqueous solution; Step 3: mixing the aldehyde-modified nanocellulose solution, the silver-ammonia solution and the glutathione solution and stirring them thoroughly to obtain silver nanocluster micelles; wherein the molar ratio of the aldehyde content of the aldehyde-modified nanocellulose, the silver-ammonia complex ions in the silver-ammonia solution and the glutathione is 1:5:7; Step 4: adding the silver nanocluster micelles to the modified sodium alginate aqueous solution, the volume ratio of the silver nanocluster micelles to the modified sodium alginate aqueous solution is 1:3, ultrasonically treating for 50 minutes and then standing for 40 minutes; Step 5: slowly pour into anhydrous ethanol solution to obtain modified sodium alginate wet gel loaded with silver nanoclusters, let stand for 1 hour, and filter; Step 6: rinse with deionized water, pre-freeze for 24 hours, and freeze-dry to obtain modified sodium alginate aerogel loaded with silver nanoclusters; Step 7: crushing the modified sodium alginate aerogel loaded with silver nanoclusters and passing it through a 400-mesh sieve to obtain aerogel particles; Step 8: dissolving polyurethane in N,N-dimethylformamide to obtain a polyurethane solution with a concentration of 0.3 g / mL, immersing aerogel particles therein, and maintaining the solution under vacuum until bubbles escape; Step 9: Take out and dry thoroughly to obtain the antibacterial / corrosion-resistant filler with a core-shell structure. Example 5

[0023] The preparation method of the core-shell structured antibacterial / corrosion-resistant filler is as follows: Step 1: Take 10 g of sodium alginate, add water and stir to obtain a 1.5 wt.% sodium alginate aqueous solution; Step 2: Take 1 g of ethylenediamine, add water and stir to obtain a 2 wt.% ethylenediamine solution, mix the sodium alginate aqueous solution and the ethylenediamine solution and stir evenly to obtain a modified sodium alginate aqueous solution; Step 3: mixing the aldehyde-modified nanocellulose solution, the silver-ammonia solution and the glutathione solution and stirring them thoroughly to obtain silver nanocluster micelles; wherein the molar ratio of the aldehyde content of the aldehyde-modified nanocellulose, the silver-ammonia complex ions in the silver-ammonia solution and the glutathione is 1:5:7; Step 4: adding the silver nanocluster micelles to the modified sodium alginate aqueous solution, the volume ratio of the silver nanocluster micelles to the modified sodium alginate aqueous solution is 1:2, ultrasonically treating for 50 minutes and then standing for 40 minutes; Step 5: slowly pour into anhydrous ethanol solution to obtain modified sodium alginate wet gel loaded with silver nanoclusters, let stand for 1 hour, and filter; Step 6: rinse with deionized water, pre-freeze for 24 hours, and freeze-dry to obtain modified sodium alginate aerogel loaded with silver nanoclusters; Step 7: crushing the modified sodium alginate aerogel loaded with silver nanoclusters and passing it through a 400-mesh sieve to obtain aerogel particles; Step 8: dissolving polyurethane in N,N-dimethylformamide to obtain a polyurethane solution with a concentration of 0.2 g / mL, immersing aerogel particles therein, and maintaining the solution under vacuum until bubbles escape; Step 9: Take out and dry thoroughly to obtain the antibacterial / corrosion-resistant filler with a core-shell structure. Example 6

[0024] The preparation method of the core-shell structured antibacterial / corrosion-resistant filler is as follows: Step 1: Take 10 g of sodium alginate, add water and stir to obtain a 1.5 wt.% sodium alginate aqueous solution; Step 2: Take 1 g of ethylenediamine, add water and stir to obtain a 2 wt.% ethylenediamine solution, mix the sodium alginate aqueous solution and the ethylenediamine solution and stir evenly to obtain a modified sodium alginate aqueous solution; Step 3: mixing the aldehyde-modified nanocellulose solution, the silver-ammonia solution and the glutathione solution and stirring them thoroughly to obtain silver nanocluster micelles; wherein the molar ratio of the aldehyde content of the aldehyde-modified nanocellulose, the silver-ammonia complex ions in the silver-ammonia solution and the glutathione is 1:5:7; Step 4: adding the silver nanocluster micelles to the modified sodium alginate aqueous solution, the volume ratio of the silver nanocluster micelles to the modified sodium alginate aqueous solution is 1:2, ultrasonically treating for 50 minutes and then standing for 40 minutes; Step 5: slowly pour into anhydrous ethanol solution to obtain modified sodium alginate wet gel loaded with silver nanoclusters, let stand for 1 hour, and filter; Step 6: rinse with deionized water, pre-freeze for 24 hours, and freeze-dry to obtain modified sodium alginate aerogel loaded with silver nanoclusters; Step 7: crushing the modified sodium alginate aerogel loaded with silver nanoclusters and passing it through a 400-mesh sieve to obtain aerogel particles; Step 8: dissolving polyurethane in N,N-dimethylformamide to obtain a polyurethane solution with a concentration of 0.4 g / mL, immersing aerogel particles therein, and maintaining the solution under vacuum until bubbles escape; Step 9: Take out and dry thoroughly to obtain the antibacterial / corrosion-resistant filler with a core-shell structure. Example 7

[0025] The preparation method of the core-shell structured antibacterial / corrosion-resistant filler is as follows: Step 1: Take 10 g of sodium alginate, add water and stir to obtain a 1.5 wt.% sodium alginate aqueous solution; Step 2: Take 1 g of ethylenediamine, add water and stir to obtain a 2 wt.% ethylenediamine solution, mix the sodium alginate aqueous solution and the ethylenediamine solution and stir evenly to obtain a modified sodium alginate aqueous solution; Step 3: mixing the aldehyde-modified nanocellulose solution, the silver-ammonia solution and the glutathione solution and stirring them thoroughly to obtain silver nanocluster micelles; wherein the molar ratio of the aldehyde content of the aldehyde-modified nanocellulose, the silver-ammonia complex ions in the silver-ammonia solution and the glutathione is 1:5:7; Step 4: adding the silver nanocluster micelles to the modified sodium alginate aqueous solution, the volume ratio of the silver nanocluster micelles to the modified sodium alginate aqueous solution is 1:2, ultrasonic treatment for 30 minutes and then standing for 40 minutes; Step 5: slowly pour into anhydrous ethanol solution to obtain modified sodium alginate wet gel loaded with silver nanoclusters, let stand for 1 hour, and filter; Step 6: rinse with deionized water, pre-freeze for 24 hours, and freeze-dry to obtain modified sodium alginate aerogel loaded with silver nanoclusters; Step 7: crushing the modified sodium alginate aerogel loaded with silver nanoclusters and passing it through a 400-mesh sieve to obtain aerogel particles; Step 8: dissolving polyurethane in N,N-dimethylformamide to obtain a polyurethane solution with a concentration of 0.3 g / mL, immersing aerogel particles therein, and maintaining the solution under vacuum until bubbles escape; Step 9: Take out and dry thoroughly to obtain the antibacterial / corrosion-resistant filler with a core-shell structure. Example 8

[0026] The preparation method of the core-shell structured antibacterial / corrosion-resistant filler is as follows: Step 1: Take 10 g of sodium alginate, add water and stir to obtain a 1.5 wt.% sodium alginate aqueous solution; Step 2: Take 1 g of ethylenediamine, add water and stir to obtain a 2 wt.% ethylenediamine solution, mix the sodium alginate aqueous solution and the ethylenediamine solution and stir evenly to obtain a modified sodium alginate aqueous solution; Step 3: mixing the aldehyde-modified nanocellulose solution, the silver-ammonia solution and the glutathione solution and stirring them thoroughly to obtain silver nanocluster micelles; wherein the molar ratio of the aldehyde content of the aldehyde-modified nanocellulose, the silver-ammonia complex ions in the silver-ammonia solution and the glutathione is 1:5:7; Step 4: adding the silver nanocluster micelles to the modified sodium alginate aqueous solution, the volume ratio of the silver nanocluster micelles to the modified sodium alginate aqueous solution is 1:2, and ultrasonic treatment is performed for 60 minutes and then allowed to stand for 40 minutes; Step 5: slowly pour into anhydrous ethanol solution to obtain modified sodium alginate wet gel loaded with silver nanoclusters, let stand for 1 hour, and filter; Step 6: rinse with deionized water, pre-freeze for 24 hours, and freeze-dry to obtain modified sodium alginate aerogel loaded with silver nanoclusters; Step 7: crushing the modified sodium alginate aerogel loaded with silver nanoclusters and passing it through a 400-mesh sieve to obtain aerogel particles; Step 8: dissolving polyurethane in N,N-dimethylformamide to obtain a polyurethane solution with a concentration of 0.3 g / mL, immersing aerogel particles therein, and maintaining the solution under vacuum until bubbles escape; Step 9: Take out and dry thoroughly to obtain the antibacterial / corrosion-resistant filler with a core-shell structure. Comparative Example 1

[0027] The difference between this embodiment and embodiment 3 is that the silver nanocluster micelles are not loaded, and silver ions are directly added, as follows: The preparation method of the core-shell structured antibacterial / corrosion-resistant filler is as follows: Step 1: Take 10 g of sodium alginate, add water and stir to obtain a 1.5 wt.% sodium alginate aqueous solution; Step 2: Take 1 g of ethylenediamine, add water and stir to obtain a 2 wt.% ethylenediamine solution, mix the sodium alginate aqueous solution and the ethylenediamine solution and stir evenly to obtain a modified sodium alginate aqueous solution; Step 3: Dissolve 7.8 mmol sodium nitrate, 6.1 mmol silver nitrate and 10 mmol ammonium dihydrogen phosphate in 100 mL distilled water to obtain a mixed aqueous solution; Step 4: adding the mixed aqueous solution to the modified sodium alginate aqueous solution, the volume ratio of the mixed aqueous solution to the modified sodium alginate aqueous solution is 1:2, ultrasonically treating for 50 minutes and then standing for 40 minutes; Step 5: slowly pour into anhydrous ethanol solution to obtain modified sodium alginate wet gel loaded with silver ions, let stand for 1 hour, and filter; Step 6: rinse with deionized water, pre-freeze for 24 hours, and freeze-dry to obtain modified sodium alginate aerogel loaded with silver ions; Step 7: crushing the modified sodium alginate aerogel loaded with silver ions, passing through a 400-mesh sieve, and obtaining aerogel particles; Step 8: dissolving polyurethane in N,N-dimethylformamide to obtain a polyurethane solution with a concentration of 0.3 g / mL, immersing aerogel particles therein, and maintaining the solution under vacuum until bubbles escape; Step 9: Take out and dry thoroughly to obtain the antibacterial / corrosion-resistant filler with a core-shell structure. Comparative Example 2

[0028] The difference between this embodiment and embodiment 3 is that ethylenediamine is not used for modification, and the details are as follows: The preparation method of the core-shell structured antibacterial / corrosion-resistant filler is as follows: Step 1: Take 10 g of sodium alginate, add water and stir to obtain a 1.5 wt.% sodium alginate aqueous solution; Step 2: mixing the aldehyde-modified nanocellulose solution, the silver-ammonia solution and the glutathione solution and stirring them thoroughly to obtain silver nanocluster micelles; wherein the molar ratio of the aldehyde content of the aldehyde-modified nanocellulose, the silver-ammonia complex ions in the silver-ammonia solution and the glutathione is 1:5:7; Step 3: adding the silver nanocluster micelles to the sodium alginate aqueous solution, the volume ratio of the silver nanocluster micelles to the sodium alginate aqueous solution is 1:2, ultrasonically treating for 50 minutes and then standing for 40 minutes; Step 4: slowly pour into anhydrous ethanol solution to obtain sodium alginate wet gel loaded with silver nanoclusters, let stand for 1 hour, and filter; Step 5: rinse with deionized water and pre-freeze for 24 hours, and freeze-dry to obtain sodium alginate aerogel loaded with silver nanoclusters; Step 6: crushing the sodium alginate aerogel loaded with silver nanoclusters and passing it through a 400-mesh sieve to obtain aerogel particles; Step 7: dissolving polyurethane in N,N-dimethylformamide to obtain a polyurethane solution with a concentration of 0.3 g / mL, immersing aerogel particles therein, and maintaining the solution under vacuum until bubbles escape; Step 8: Take out and dry thoroughly to obtain the antibacterial / corrosion-resistant filler with a core-shell structure. Comparative Example 3

[0029] The difference between this embodiment and embodiment 3 is that polyurethane is not used for coating, as follows: The preparation method of the antibacterial / corrosion-resistant filler is: Step 1: Take 10 g of sodium alginate, add water and stir to obtain a 1.5 wt.% sodium alginate aqueous solution; Step 2: Take 1 g of ethylenediamine, add water and stir to obtain a 2 wt.% ethylenediamine solution, mix the sodium alginate aqueous solution and the ethylenediamine solution and stir evenly to obtain a modified sodium alginate aqueous solution; Step 3: mixing the aldehyde-modified nanocellulose solution, the silver-ammonia solution and the glutathione solution and stirring them thoroughly to obtain silver nanocluster micelles; wherein the molar ratio of the aldehyde content of the aldehyde-modified nanocellulose, the silver-ammonia complex ions in the silver-ammonia solution and the glutathione is 1:5:7; Step 4: adding the silver nanocluster micelles to the modified sodium alginate aqueous solution, the volume ratio of the silver nanocluster micelles to the modified sodium alginate aqueous solution is 1:2, ultrasonically treating for 50 minutes and then standing for 40 minutes; Step 5: slowly pour into anhydrous ethanol solution to obtain modified sodium alginate wet gel loaded with silver nanoclusters, let stand for 1 hour, and filter; Step 6: rinse with deionized water, pre-freeze for 24 hours, and freeze-dry to obtain modified sodium alginate aerogel loaded with silver nanoclusters; Step 7: The modified sodium alginate aerogel loaded with silver nanoclusters is crushed and passed through a 400-mesh sieve to obtain aerogel particles.

[0030] The porosity, compressive strength and antibacterial effect of the core-shell structured antibacterial / corrosion-resistant filler of the above embodiment were measured, and the results are shown in Table 1 below: Table 1

[0031] After comprehensively comparing the various properties of the above embodiments, the antibacterial / corrosion-resistant filler with a core-shell structure prepared in Example 3 was selected for subsequent tests. Example 9

[0032] A method for preparing an antibacterial and corrosion-resistant EVA liquid storage bag material comprises the following steps: (1) The core-shell structured antibacterial / corrosion-resistant filler and the EVA substrate are uniformly mixed at a mass ratio of 3:100; (2) Place the mixture in a mixer and mix it at a mixing temperature of 110°C and a double-roll speed of 100 r / min. Mix it twice, with each mixing time being 10 min. Example 10

[0033] A method for preparing an antibacterial and corrosion-resistant EVA liquid storage bag material comprises the following steps: (1) Mixing the antibacterial / corrosion-resistant filler of the core-shell structure and the EVA substrate in a mass ratio of 4:100; (2) Place the mixture in a mixer and mix it at a mixing temperature of 110°C and a double-roll speed of 100 r / min. Mix it twice, with each mixing time being 10 min. Embodiment 11

[0034] A method for preparing an antibacterial and corrosion-resistant EVA liquid storage bag material comprises the following steps: (1) Mixing the antibacterial / corrosion-resistant filler of the core-shell structure and the EVA substrate in a mass ratio of 5:100; (2) Place the mixture in a mixer and mix it at a mixing temperature of 110°C and a double-roll speed of 100 r / min. Mix it twice, with each mixing time being 10 min. Comparative Example 4

[0035] The difference between this embodiment and embodiment 10 is that the antibacterial / corrosion-resistant filler with a core-shell structure prepared in comparative example 1 is used, specifically: A method for preparing an antibacterial and corrosion-resistant EVA liquid storage bag material comprises the following steps: (1) Mixing the antibacterial / corrosion-resistant filler of the core-shell structure and the EVA substrate in a mass ratio of 4:100; (2) Place the mixture in a mixer and mix it at a mixing temperature of 110°C and a double-roll speed of 100 r / min. Mix it twice, with each mixing time being 10 min. Comparative Example 5

[0036] The difference between this embodiment and embodiment 10 is that the antibacterial / corrosion-resistant filler with a core-shell structure prepared in comparative example 2 is used, specifically: A method for preparing an antibacterial and corrosion-resistant EVA liquid storage bag material comprises the following steps: The antibacterial / corrosion-resistant filler of the core-shell structure with a mass ratio of 4:100 was evenly mixed with the EVA substrate; (2) Place the mixture in a mixer and mix it at a mixing temperature of 110°C and a double-roll speed of 100 r / min. Mix it twice, with each mixing time being 10 min. Comparative Example 6

[0037] The difference between this embodiment and embodiment 10 is that the antibacterial / corrosion-resistant filler prepared in comparative example 3 is used, specifically: A method for preparing an antibacterial and corrosion-resistant EVA liquid storage bag material comprises the following steps: (1) Mixing the antibacterial / corrosion-resistant filler and the EVA substrate in a mass ratio of 4:100; (2) Place the mixture in a mixer and mix it at a mixing temperature of 110°C and a double-roll speed of 100 r / min. Mix it twice, with each mixing time being 10 min.

[0038] Corrosion resistance test: The initial EVA liquid storage bag material and the EVA liquid storage bag material after being soaked in 30% NaCl solution and 15% ammonia water for 6 months were tested for tensile strength and elongation at break of the liquid storage bag material prepared in each embodiment using a universal mechanical testing machine. The average value of five samples was taken. The stretching speed was 50 mm / min, and the stretching error was less than ±0.5%. The results are shown in Table 2 below: Table 2

[0039] The antibacterial rate of the liquid storage bag material of each embodiment was measured by the oscillating flask method and calculated using the following formula:

[0040] Where A is the average colony count after sample oscillation, and B is the average colony count before sample oscillation.

[0041] Table 3 .

Claims

1. An antibacterial and corrosion-resistant EVA liquid storage bag material, characterized in that: The EVA liquid storage bag material is obtained by blending an antibacterial / corrosion-resistant filler with a core-shell structure and EVA; the mass ratio of the antibacterial / corrosion-resistant filler with a core-shell structure to EVA is (3-5):100; The preparation method of the antibacterial / corrosion-resistant filler of the core-shell structure is as follows: Step 1: Take sodium alginate, add water and stir to obtain a 1.5wt.% sodium alginate aqueous solution; Step 2: Add 2wt.% ethylenediamine solution, mix and stir evenly to obtain a modified sodium alginate aqueous solution; Step 3: Mix the aldehyde-modified nanocellulose solution, the silver ammonia solution and the glutathione solution and stir them thoroughly to react, thereby obtaining silver nanocluster micelles; Step 4: Add the silver nanocluster micelles into the modified sodium alginate aqueous solution, ultrasonicate for 30-60 minutes, and then stand for 40 minutes; Step 5: slowly pour into anhydrous ethanol solution to obtain modified sodium alginate wet gel loaded with silver nanoclusters, let stand for 1 hour, and filter; Step 6: rinse with deionized water, pre-freeze for 24 hours, and freeze-dry to obtain modified sodium alginate aerogel loaded with silver nanoclusters; Step 7: crushing the modified sodium alginate aerogel loaded with silver nanoclusters, and passing it through a 400-mesh sieve to obtain aerogel particles; Step 8: dissolving polyurethane in N,N-dimethylformamide to obtain a polyurethane solution, impregnating aerogel particles therein, and maintaining the solution under vacuum until bubbles escape; Step 9: Take out and dry thoroughly to obtain the antibacterial / corrosion-resistant filler with a core-shell structure.

2. The antibacterial and corrosion-resistant EVA liquid storage bag material according to claim 1, characterized in that: The mass ratio of the sodium alginate in step 1 to the ethylenediamine in step 2 is 10:

1.

3. The antibacterial and corrosion-resistant EVA liquid storage bag material according to claim 1, characterized in that: The preparation method of the aldehyde-modified nanocellulose in step 3 is as follows: (1) Disperse cellulose in a mixed solution of sodium hydroxide, urea and thiourea, stir vigorously for 30 min, cool to -10 °C, and centrifuge at 11000 rpm for 20 min to obtain a cellulose solution; (2) Slowly dripping deionized water into the cellulose solution while slowly stirring to obtain a milky white suspension, and washing the suspension with deionized water until the pH value is 7; (3) Ultrasonication at 600 W for 30 min to obtain nanocellulose; (4) adding sodium periodate to a 10 mg / mL nanocellulose solution, adjusting the pH value to 4.5, stirring at 40 °C for 4 h, and centrifuging and washing to obtain dialdehyde nanocellulose; (5) Disperse the dialdehyde nanocellulose in deionized water, add 25 wt% glutaraldehyde solution, stir and react at 70 °C for 30 min, and wash by centrifugation with deionized water to obtain aldehyde-modified nanocellulose.

4. The antibacterial and corrosion-resistant EVA liquid storage bag material according to claim 3, characterized in that: In the mixed solution of sodium hydroxide, urea and thiourea in step (1), the concentration of sodium hydroxide, the concentration of urea and the concentration of thiourea are 8 wt %, 8 wt % and 6.5 wt %.

5. The antibacterial and corrosion-resistant EVA liquid storage bag material according to claim 3, characterized in that: In the step (4), the mass ratio of sodium periodate to nanocellulose is 2:

1.

6. The antibacterial and corrosion-resistant EVA liquid storage bag material according to claim 1, characterized in that: In the step 3, the molar ratio of the aldehyde content of the aldehyde-modified nanocellulose, the silver-ammonia complex ions in the silver-ammonia solution, and glutathione is 1:(3-8):(5-10).

7. The antibacterial and corrosion-resistant EVA liquid storage bag material according to claim 1, characterized in that: In step 4, the volume ratio of the silver nanocluster micelles to the modified sodium alginate aqueous solution is 1:(1-3).

8. The antibacterial and corrosion-resistant EVA liquid storage bag material according to claim 1, characterized in that: The concentration of the polyurethane solution in step 8 is 0.2-0.4 g / mL.

9. The method for preparing an antibacterial and corrosion-resistant EVA liquid storage bag material according to any one of claims 1 to 8, characterized in that: The following steps are involved: (1) Mixing the core-shell structured antibacterial / corrosion-resistant filler and the EVA substrate uniformly; (2) Place the mixture in a mixer and mix it at a mixing temperature of 110°C and a double-roll speed of 100 r / min. Mix it twice, with each mixing time being 10 min.

Citation Information

Patent Citations

  • Lentinan sulfate and nano silver self-assembled modified polyurethane material and preparation method

    CN101838455A

  • Green and quick preparation method of antibacterial material sodium alginate-ascorbic acid nano-silver

    CN107716943A

  • Preparation method of cellulose-graphene oxide-chitosan ternary composite aerogel

    CN109517212A

  • Preparation of silver nanocluster fluorescent composite membrane and application of silver nanocluster fluorescent composite membrane in detection of heavy metals

    CN115674739A

  • Thermally stable, dispersible cellulose nanocrystals

    US20170037155A1